At the Borders of the Regnum of Naples. The Guglia and the Princes of Taranto Orsini del Balzo in Soleto - Pollini, Giulia (Actual Problems of Theory and History of Art, 2019)
Founded in Norman times, the Principality of Taranto was a satellite area at the borders of various kingdoms, passing to Swabians and Angevins. Under the governor of the central power, its Princes were chosen among the ruling families to control the territory better and take advantage of its natural geographical strategy, especially for trade with the Adriatic Sea and the East. The exception to this long series of rulers was the Orsini del Balzo family, with its two representatives Raimondo († 1406) and his son Giovanni Antonio (†1463), totally focused on making the fief firmer thanks to some separatist tendencies from the Crown. After the election of Raimondo Orsini del Balzo as Prince of Taranto in 1399, many artistic centres flourished insmall towns. An example is the magnificent basilica of S. Caterina in Galatina (near Lecce) founded by Raimondo,which houses Princes’ tombs and well–known frescoes of the beginning of the 15th century. A few kilometres away from Galatina, the small town of Soleto was invested with new importance by the Orsini del Balzo. The core of the homonymous County, it reached its maximum territorial expansion during that time. Here there are several sites celebrating the glories of the family, but the most important one is the so-called Guglia, a belfry, approximately 45 m tall, decorated with sculptures and coats of arms, leant against the façade of the Church of Maria Santissima Assunta. The paper is focused on the analysis of this monument,variously dated between the end of the 14th century and the first half of the 15th century and differently linked to Raimondo or Giovanni Antonio. Even though not so many years passed between the governments of the father and the son, their patronages were really dissimilar: the first was devoted to the tradition of Romanesque art, whereas the second focused on a language receptive to the International Gothic. This study wants to endorse the figure of Giovanni Antonio as commissioner of the tower and highlights the political importance of this piece of art declaring the power of the family in a territory at the borders of the Kingdom of Naples.